Oxidation resistance and mechanical properties of LaB6-MoSi2-SiC ceramic coating toughened by SiC nanowires. Issue 14 (1st October 2018) - Wang, Changcong; Li, Kezhi; He, Qinchuan; Su, Yangyang; Huo, Caixia; Shi, Xiaohong
Abstract: To improve the high-temperature tolerance of carbon/carbon composites, a compact SiC-nanowires toughened LaB6 -MoSi2 -SiC/SiC (SiCnws-LMS/SiC) coating was designed and fabricated by combination of multiple methods including pack cementation, chemical vapor deposition and supersonic atmospheric plasma spraying. Isothermal oxidation results indicated that the mass loss of LMS/SiC coating decreased from 4.34 ± 0.28% to 1.12 ± 0.23% after oxidation for 200 h at 1773 K benefit from the addition of SiCnws. Absence of obvious cracks and voids in the coating after oxidation test indicated that the interfaces between various phases and SiCnws could obstruct the crack propagation by releasing the thermal stress in the coating. Meanwhile, after the introduction of SiCnws, the bonding strength and flexural strength of the coating were respectively increased by 54.54% and 59.77% compared to the LMS/SiC coating without SiCnws. The improved mechanical properties could be attributed to the pullout and bridging effects of SiCnws, which created multi-scaled reinforcements, thereby enhancing the load bearing capacity to increase the fracture toughness of the coating.